Solar technology applied to water purification - Rodriguez, Juan (2010)
Drinking water is extremely scarce good in the world. Of the estimated 1.4 billion cubic kilometers of water on earth, 97.6% is salt, 2.38% is like ice and glaciers and only about 0.024% is above the earth's surface and therefore may be destined for human consumption. In this situation, the lack of access to drinking water is a serious problem in the world and Peru is no exception. Of the 6 billion people who inhabit the land, over a billion suffer from this problem. However, about 2.5 billion lack access to adequate sanitation. This means that more than 6 million children a year die from diseases that are caused by the water they consume.